Transforming Learning Environments with Information Technology: Trends and Best Practices - Rahayu, Sri (CV. Creative Tugu Pena, 2023)
This research was conducted as a way to examine contextual factors in the effective application of information technology to help the learning environment which can help carry out transformation in the field of education as a new learning method. The research method used is a qualitative descriptive method by prioritizing library or literature studies in the research process. By referring to the design components and also the implementation of initiatives in the field of education as a way of educational transformation, this research can describe what happens with the advancement of information technology to transformation in the world of education and learning which is also related to the integration of technology, policy recommendations, and also resources. sustainable power. The transformation of the education system of course supports national competitiveness as one of the long-term efforts that receives continuous support and also visionary leadership in providing input for the world of education with the help of advanced information technology. Keywords: Learning Environments, Information Technology, Effective Application